2021
DOI: 10.3390/ijms22094870
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Betulinic Acid Cytotoxicity and Mitochondrial Metabolism Impairment in a Human Melanoma Cell Line

Abstract: Melanoma represents one of the most aggressive and drug resistant skin cancers with poor prognosis in its advanced stages. Despite the increasing number of targeted therapies, novel approaches are needed to counteract both therapeutic resistance and the side effects of classic therapy. Betulinic acid (BA) is a bioactive phytocompound that has been reported to induce apoptosis in several types of cancers including melanomas; however, its effects on mitochondrial bioenergetics are less investigated. The present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 62 publications
3
35
0
Order By: Relevance
“…The current results indicate the following: (i) BA at low concentrations (< 50 µM) exerts a selective cytotoxicity (HDFa cells' viability was not affected, while in melanoma cells was significantly decreased -Figures 2, 4 and 6), still by increasing the concentration the selectivity is lost; and (ii) BA treatment proved to be highly cytotoxic on both pigmented (B16-F10) and non-pigmented (SK-MEL-5) cells (with a higher susceptibility recorded in the case of SK-MEL-5) by decreasing cells' viability percentages and by inducing morphological changes in melanoma cells shape, changes that indicate an apoptosis-like effect. The selectivity of BA towards cancer cells and a lack/a very low toxicity against healthy cells was also described in previous studies [21,31].…”
Section: Resultssupporting
confidence: 65%
See 4 more Smart Citations
“…The current results indicate the following: (i) BA at low concentrations (< 50 µM) exerts a selective cytotoxicity (HDFa cells' viability was not affected, while in melanoma cells was significantly decreased -Figures 2, 4 and 6), still by increasing the concentration the selectivity is lost; and (ii) BA treatment proved to be highly cytotoxic on both pigmented (B16-F10) and non-pigmented (SK-MEL-5) cells (with a higher susceptibility recorded in the case of SK-MEL-5) by decreasing cells' viability percentages and by inducing morphological changes in melanoma cells shape, changes that indicate an apoptosis-like effect. The selectivity of BA towards cancer cells and a lack/a very low toxicity against healthy cells was also described in previous studies [21,31].…”
Section: Resultssupporting
confidence: 65%
“…In another study developed by Farcas et al, it has been revealed that BA decreases the viability of B164A5 and A375 MM cells at the concentrations of 5 and 25 µM following 24 and 48 h [34]. In a recent study by Coricovac et al, BA is shown to induce a dose-dependent cytotoxicity in A375 MM cells after 24 h, accompanied by apoptotic nuclear features (shrinkage, chromatin condensation), up-regulation of pro-apoptotic markers (Bax, Bad, and Bak), inhibition of mitochondrial respiration and glycolysis, and decrease in the mitochondrial membrane potential [21]. A very recent study showed that BA proved to be very active against equine melanoma cells [35].…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations